Adhesive- and Metal-Free Assembly Techniques for Prefabricated Multi-Layer Engineered Wood Products: A Review on Wooden Connectors - Han, Lei; Kutnar, Andreja; Sandak, Jakub; Šušteršič, Iztok; Sandberg, Dick (Forests, 2023)
Engineered wood products (EWPs) are being increasingly used as construction materials. EWPs are currently being made using synthetic adhesives or metal fasteners, which lead to poor recyclability and reusability. Therefore, this review paper focused on emerging adhesive- and metal-free assembling techniques including wood dowels, rotary-dowel welding, wooden nails, and dovetail joining as alternative ways of making prefabricated EWPs. This will contribute towards green construction and optimising the building process to minimise its negative impact on the environment and its inhabitants, while maximising the positive aspects of the finished structure. The respective advantages and shortcomings will be compared with those of equivalent EWPs. In general, the dowel-laminated timber (DLT) provides sufficient load-bearing capacity and even better ductility than EWPs of equivalent size, but its relatively low stiffness under a bending load limits its application as a structural element. Optimised manufacturing parameters such as dowel species, dowel spacing, dowel diameter, dowel insertion angle, dowel shape, etc. could be studied to improve the stiffness. The improved mechanical properties and tight fitting due to set-recovery of densified wood support its use as sustainable alternatives to hardwood dowels in DLT to overcome problems such as the loosening of connections over time and dimensional instability. The rotary welding technology could also enhance the strength and long-term performance of dowel-type joints, but its poor water resistance needs further investigation. The main obstacles to implementing DLT products in the market are missing technical information and design guidelines based on national codes. Validerad;2023;Nivå 2;2023-02-13 (hanlid); Funder: Republic of Slovenia; Slovenian Research Agency ARRS (J4-3087); CT WOOD, Luleå University of Technology